Surface-localized magnetic order in RuO2 thin films revealed by low-energy muon probes - Akashdeep, Akashdeep; Krishnia, Sachin; Ha, Jae-Hyun; An, Siyeon; Gaerner, Maik; Prokscha, Thomas; Suter, Andreas; Janka, Gianluca; Reiss, Gunter; Kuschel, Timo; Han, Dong-Soo; Di Bernardo, Angelo; et al. (American Institute of Physics, 2026)
Ruthenium dioxide (RuO2) has recently emerged as an altermagnetic candidate, but its intrinsic magnetic ground state in thin films remains widely debated. This study aims to clarify the nature and spatial extent of the magnetic order in RuO(2 )thin films grown under different conditions. Thin films of RuO2 with thicknesses of 30 and 33 nm are deposited by pulsed laser deposition and sputtering onto TiO2(110) and Al2O3( 1<overline>102) substrates, respectively. Low-energy muon spin rotation/relaxation (LE- mu SR) with depth-resolved sensitivity measurements is performed in transverse magnetic fields (TF) from 4 K to 290 K. The mu SR data collected with a muon implantation energy of 1 keV reveal that magnetic signals originate from the near-surface region of the film ( less than or similar to 10 nm), and the affected volume fraction is approximately 8.5%. The localized magnetic response is consistent across different substrates, growth techniques, and parameter sets, suggesting a common origin related to surface defects and dimensionality effects. The combined use of TF- mu SR and the study of depth-dependent implantation with low-energy muons provides direct evidence for surface-confined, inhomogeneous static magnetic order in RuO2 thin films, helping reconcile discrepancies. These findings underscore the importance of considering reduced-dimensional contributions and motivate further investigation into the role of defects, strain, and stoichiometry on the magnetic properties of RuO2, especially at the surface.